Health personnel's experience with resident-centered care in nursing homes in Korea: A qualitative study - HeeKyung Chang (Elsevier, 2019)
Objectives: Changing the culture in nursing homes in South Korea comes with challenges, and the key issues of resident-centered care have been described. This study aims to describe health personnel's experience in providing resident-centered care in nursing homes. Methods: Qualitative data were collected through individual and focus group interviews consisting of registered nurses (n = 4), certified nurse assistants (n = 2), and long-term caregivers (n = 12) working at nursing homes in South Korea. The participants (n = 18) completed the interviews from May to June 2018, and all interviews were recorded, transcribed, and analyzed by employing the content analysis method. Results: Five main categories are conceptualized: (1) residents' participation in decision making, (2) the sharing of the history and story of residents, (3) the recognition of facility- or task-based attitudes, (4) the guarantee of private time and space for residents, and (5) the need for standardized guidelines. Conclusions: Results corroborate that health personnel regard resident-centered care as a desirable nursing paradigm. However, facility- or task-centered care is the most effective in hectic situations. A standardized protocol on the application of resident-centered care based on the facility-tailored specification is unavailable. Therefore, health personnel's perception and practice of resident-centered care can differ. Efficient nursing intervention programs should be developed after clarifying facility culture. Keywords: Aged, Nursing care, Qualitative research, Skilled nursing facilities